Higher levels of Hepatocyte Growth Factor (HGF) in human seminal plasma in comparison with blood plasma and negative association with several motile sperm cells - Anders Larsson; Lena Carlsson; Rasha Khierallah; Jan Holte; Theodora Kunovac Kallak (Global Journal of Fertility and Research - Peertechz Publications, 2023)
Context: Semen is a complex fluid with many functions, some of them well-known, others more obscure.  Aims: The aim of this study was to investigate the levels of Hepatocyte Growth Factor (HGF) in human seminal plasma in comparison with blood plasma levels.  Methods: HGF concentrations were measured in seminal plasma from 40 men utilizing commercial ELISA kits. Blood plasma from 40 healthy blood donors served as a comparison group.  Results: Median seminal plasma HGF was approximately five times higher than the levels found in blood plasma (5717.5 pg/mL vs. 1124.6 pg/mL). There was a negative correlation between HGF values in seminal plasma and the number of sperm cells.  Conclusion: The study shows that seminal plasma contains high levels of HGF and that HGF binds to prostasomes. Male HGF can thus reach the female reproductive tract during unprotected sexual intercourse. Further studies are warranted to evaluate the effect of this on fertility.